THE EFFECT OF PROFITABILITY AND SOLVENCY ON STOCK RETURNS MODERATED BY MACROECONOMIC - Agustine, Aurel; Hermuningsih, Sri; Hidayat, Riskin (SULTANIST: Jurnal Manajemen dan Keuangan, 2024)
The purpose of this study was to examine the effect of profitability and solvency on stock returns moderated by macroeconomic. The population of this study are companies listed on the Sri Kehati index with purposive sampling technique. The analysis used is PLS-SEM using SmartPLS 3.0 software. The analysis in this study was carried out by testing the outer model and inner model.  This study shows that profitability has an insignificant positive effect on stock returns, solvency has a significant positive effect on stock returns, macroeconomic weakens the effect of profitability on stock returns, and macroeconomic strengthens the effect of solvency on stock returns.